Photobleaching and Recovery of Symbiodiniaceae Effrenium voratum SCS01 Reveals Life Form Transformation Under Thermal Stress - Sanqiang Gong (Frontiers Media S.A., 2021)
Dinoflagellates in the family Symbiodiniaceae contain a number of species and play an important role in the establishment of coral reef ecosystems in oligotrophic marine waters. Effrenium voratum is likely an exclusively free-living and heterotrophic species of Symbiodiniaceae. How this species responds and acclimates to warming is largely unknown. The present study experimentally established the phenotypic landscapes related to the photobleaching and recovery processes of Effrenium voratum SCS01 following thermal stress. We found that thermal stress bleached the plastids of E. voratum SCS01 and caused the cells to become lighter in color. Thereafter, the bleached cells recovered rapidly when they returned to the optimal temperature. The dominant life form of E. voratum SCS01 shifted from mastigote cells to coccoid cells then returned to mastigote cells. Transcriptome analysis revealed that the photobleaching of E. voratum SCS01 was due to increased degradation and decreased biosynthesis of photosynthetic pigments. The thermally induced life form changes were related to the downregulation of genes for cell motility. Our results revealed the mechanism of photobleaching in E. voratum SCS01 and indicated life form transformation as a newly identified survival strategy of Effrenium voratum SCS01 under thermal stress.